2013
DOI: 10.1002/htj.21113
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Convection Effect on Melting from a Vertical Plate Embedded in Porous Medium with Soret and Dufour Effects

Abstract: The present work analyzed the impact of mixed convection on melting from a vertical flat plate embedded in porous medium in the presence of Dufour and Soret effects. The partial differential equations governing the problem under consideration have been transformed by a similarity transformation into a system of ordinary differential equation which is solved numerically by Runge-Kutta-Gill methods. Dimensionless velocity, temperature, and concentration profiles are presented graphically for various values of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…The phenomenon of natural convection boundary layer flow over flat plates has received a great deal of attention from the research community . Numerous studies have reported on the natural convection flow past vertical or inclined flat plates …”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of natural convection boundary layer flow over flat plates has received a great deal of attention from the research community . Numerous studies have reported on the natural convection flow past vertical or inclined flat plates …”
Section: Introductionmentioning
confidence: 99%